ECONOMIC SAFETY IN THE CONTEXT OF COMMERCIAL TRANSACTIONS - Joksts, Jānis (Administrative and Criminal Justice, 2018)
Raiderism is a type of offense that doesn’t have an exact definition in the law system. The main goal of the publication is to investigate the topicality of the fraudulent version – the raiderism and research historical interrelationships in the aspect of normative acts, as well as to study the nature of raiderism by analyzing a specific example. This example, like many others, fully confirms the hypothesis of the existence of raiderism, the problem of preventative identification of the profile of riders, as well as the imperfections of normative acts. In author’s opinion, it is possible to identify the most common types and by providing appropriate solutions to the regulatory of the area – raiderism can be localized quickly, but perpetrators can be held liable for their actions. Undoubtedly, effective regulatory regulation will also act as a deterrent to the spread of raiderism, as the inability to react effectively and the relative sense of impunity serve as catalyst for the raiders – the injured party needs to make great efforts and, despite the losses caused by the raiders, must be financially capable of proving the perpetrator’s offense in long term.